Biodegradation of carboxymethylcellulose using Pleurotus : oligosaccharides production and fermentable sugars for ethanol industry - Barreto, Andressa Ribas; Silva, Ísis Serrano; Dias, Elisangela Franciscon Guimaro; Durrant, Lucia Regina; Menezes, Cristiano Ragagnin de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this present study, white-rot fungi Pleurotus sp BCCB068 were evaluated as regards the degradation of the cellulose matrix with production of enzymes using submerged fermentation.The crude extract obtained from the fungi growths was used as enzyme source for carboxymethylcellulose hydrolysis, reached 54.8% of degradation during 0-60 minutes of reaction period, with formation of oligosaccharides, as well as several sugar monomers (cellobiose, mannose, maltose, fructose and glucose). These results indicate great potential of these fungal strains to degrade cellulosic materials and produce sugar monomers to be used in ethanol industries.